Wide band gap semiconductor technology: State-of-the-art. (May 2019) - Shur, Michael
Abstract: Applications of the wide band gap (WBG) semiconductors, such as GaN, AlGaN, and InGaN, range from lighting and ultraviolet (UV) technology to high power, radiation hard, high temperature, terahertz (THz) and sub-THz electronics and pyroelectronics. Wurtzite (hexagonal) symmetry makes these materials to be quite different from conventional cubic semiconductors. Spontaneous and piezoelectric polarization associated with the wurtzite crystal structure induces two-dimensional electron gases at AlGaN/GaN, AlInN/GaN, and AlGaN/InGaN interfaces with sheet concentrations 10–20 times higher than those in Si CMOS. A high current carrying capability and a high breakdown field make these materials perfect for high power applications. Adjusting the energy gaps of Alx Ga1−x N and of Inx Ga1−x N by varying the molar fraction changes the wavelength of light they emit or absorb and enables light and UV emitters, solar cells, and photodetectors operating from THz and infrared to deep UV range. Blue, green, and white LEDs using InGaN revolutionized smart solid-state lighting. AlGaN UV LEDs are used for water purification, fighting antibiotic resistant bacteria and viruses, and dramatically increasing produce storage time. InN, ZnO, and BN have potential to compete with the AlN/GaN family. Diamond has re-emerged not only as a substrate for a record heat removal but also as a viable THz detector material. The WBG technology has many difficult problems to solve. High dislocation density in the WBG materials leads to a low efficiency of deep AlGaN UV LEDs and reliability problems of high power devices. Non-uniformities of the electric field distribution cause a premature breakdown. Using ultrathin WBG quantum well layers and nanowires and exploring radically new physics-based device designs might alleviate or even solve these problems.